Real-world efficacy and safety of 8 mg aflibercept in neovascular AMD: a case series - David A Eichenbaum; Deepak Sambhara; Priya Vakharia (BMJ Open Ophthalmology, 2025)
Objective This real-world retrospective case series evaluates the safety and efficacy of aflibercept 8 mg in patients diagnosed with neovascular age-related macular degeneration (nAMD).Methods and analyses Treatment-naïve or treatment-experienced patients with nAMD receiving aflibercept 8 mg with at least 6 months of follow-up were assessed.Results 40 eyes from 33 patients were included, of which 36/40 eyes were previously treated. The mean age of subjects is 79.84 years. At baseline, 29/36 eyes had intraretinal fluid (IRF)/subretinal fluid (SRF) at an average interval of 40.97 days, logMAR VA of 0.346, and average central subfield thickness (CST) of 341.53 µm. At final follow-up, average logMAR VA was 0.315 and average CST decreased by 39.39 µm, with an average number of days since last treatment of 52.9. Of the 32 eyes with IRF, SRF, or both at the time of switch, 12 eyes achieved anatomical quiescence without IRF/SRF after the first injection of aflibercept 8 mg, including three of four treatment-naive patients.Conclusions This early case series suggests that patients treated with aflibercept 8 mg may achieve greater duration between treatments while preserving and, in some cases, improving visual acuity and anatomical outcomes in a real-world clinic setting. In this retrospective study, the patient population primarily consisted of treatment-experienced cases with recalcitrant disease or high treatment burdens, potentially using aflibercept 8 mg as salvage therapy. This selection bias limits generalisability to broader real-world populations. The small sample size precludes formal statistical conclusions. Multiple investigators made unstandardised treatment decisions based on individual clinical judgement, including whether to continue aflibercept 8 mg or revert to prior therapy, sometimes after just one injection.